Identification of plasma proteins binding oxidized phospholipids using pull-down proteomics and OxLDL masking assay‡ - Philipp Jokesch; Lisa Holzer; Lydia Jantscher; Sebastian Guttzeit; Rudolf Übelhart; Olga Oskolkova; Valery Bochkov; Bernd Gesslbauer (Journal of Lipid Research)
Oxidized phospholipids (OxPLs) are increasingly recognized as toxic and proinflammatory mediators, which raises interest in the mechanisms of their detoxification. Circulating OxPLs are bound and neutralized by plasma proteins, including both antibodies and non-immunoglobulin proteins. The latter group of proteins is essentially not investigated because only three OxPC-binding plasma proteins are currently known. The goal of this work was to characterize a broad spectrum of plasma proteins selectively binding OxPLs. Using pull-down-proteomic analysis, we found about 150 non-immunoglobulin proteins preferentially binding oxidized 1-palmitoyl-2-arachidonoyl-sn-glycero-phosphatidylcholine (OxPAPC) as compared to non-oxidized PAPC. To test if candidate proteins indeed can form a barrier isolating OxPLs from recognition by other proteins, we applied an immune masking assay. Oxidized LDL (OxLDL) immobilized in multiwell plates was used as a carrier of OxPLs, while mAbs recognizing OxPC or OxPE were used as “detectors” showing if OxPLs on the surface of OxLDL are physically accessible to external binding partners. Using an orthogonal combination of pull-down and masking assays we confirmed that previously described OxPL-binding proteins (non-fractionated IgM, CFH, and Apo-M) indeed can bind to and mask OxPC and OxPE on liposomes and OxLDL. Furthermore, we identified additional plasma proteins selectively binding and masking OxPC including Apo-D, Apo-H, pulmonary surfactant-associated protein B, and antithrombin-III. We hypothesize that in addition to circulating antibodies, multiple non-immunoglobulin plasma proteins can also bind OxPLs and modulate their recognition by innate and adaptive immunity.